Method for producing high-gloss wear-resistant inorganic ecological stone by dry method

The production of high-gloss wear-resistant inorganic ecological stones through dry process solves the problems of high energy consumption, environmental pollution and performance limitations in the wet process, and achieves an efficient and environmentally friendly production process, meeting the market's demand for high-gloss wear-resistant ecological stones.

CN119551959AActive Publication Date: 2025-03-04SHANDONG ZHOULEI NEW BUILDING MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411755168.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing wet process produces inorganic ecological stones with high energy consumption, environmental pollution, performance limitations and insufficient sustainability, which is difficult to meet the market's demand for high-gloss wear-resistant ecological stones.

Method used

The dry process is used to produce high-gloss and wear-resistant inorganic ecological stones. By uniformly mixing cement, industrial by-product gypsum, mineral powder, industrial slag, construction waste and tailings, high-density boards are pressed using a hydraulic press, and after steaming and curing, the stone brightener is used for polishing.

Benefits of technology

It significantly improves the gloss and wear resistance of inorganic ecological stones, reduces energy consumption and pollution, meets the market's demand for high-gloss wear-resistant ecological stones, and conforms to the development direction of green building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166083680000071
    Figure BDA0005166083680000071
  • Figure BDA0005166083680000081
    Figure BDA0005166083680000081
Patent Text Reader

Abstract

The invention discloses a method for producing high-gloss wear-resistant inorganic ecological stone by a dry method, and relates to the field of building materials. The method comprises the following steps: mixing cement, industrial byproduct gypsum, mineral powder, industrial slag, building waste, tailings, marble, sand and a stone brightener in proportion, and carrying out material distribution, pressing, steam curing, curing, polishing and the like to obtain the high-gloss wear-resistant inorganic ecological stone slab. The process has the advantages of high solid waste utilization rate, low production energy consumption, high product surface luminosity, excellent wear resistance, environmental protection, no pollution and the like, and is suitable for wide application in the building decoration industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, in particular to a method for producing high-gloss wear-resistant inorganic ecological stone by dry method. Background Art

[0002] Inorganic eco-stone is a high-performance building decoration material made of solid waste as the main component through a specific process. With its advantages of environmental protection, durability, high compressive strength and elegant appearance, it is widely used in floor paving, wall decoration and furniture manufacturing, and has gradually become an important choice of green and environmentally friendly materials in the modern construction industry.

[0003] For example, patent document CN114507081B discloses a preparation process of an inorganic ecological stone and an inorganic ecological stone that maintains high brightness, which relates to the field of inorganic stone preparation technology. The preparation process includes the following steps: (1) a large particle pretreatment liquid filling treatment step, (2) a small particle high-gloss nano-liquid high-gloss treatment step, and (3) a brightening and waterproofing liquid brightening and waterproofing treatment step.

[0004] However, the inorganic eco-stone production process currently on the market is mainly based on the wet method, which usually requires a large amount of water to mix and shape the materials. This traditional production method has the following shortcomings:

[0005] High energy consumption: In the wet process, the mixing, molding and subsequent maintenance of materials require high energy consumption, especially in the drying stage, which consumes a lot of energy, reducing production efficiency and economy. Environmental pollution: The wet process will produce a large amount of wastewater containing dissolved chemical additives and material particles. If the wastewater is not properly treated, it will cause serious pollution to the environment. In addition, the dust and noise pollution problems generated during the production process are also prominent. Performance limitations The surface gloss and wear resistance of the eco-stone produced by the wet process are often low. Due to excessive moisture in the mixing and molding process, the product is prone to internal cracks or pores in the subsequent drying and maintenance stages, which reduces the density and mechanical properties of the product. Insufficient sustainability: Traditional production processes make it difficult to fully utilize solid wastes such as industrial by-product gypsum, industrial slag, construction waste and tailings. Some wastes and by-products are directly discarded or processed, which increases production costs and wastes resources, and is not conducive to the realization of sustainable development goals. High requirements for process precision: The wet process is highly dependent on the mixing ratio, moisture control, and ambient temperature and humidity. Any inappropriateness may lead to unstable product quality and make it difficult to meet the performance requirements of high-gloss, wear-resistant, and high-density products.

[0006] In recent years, with the diversification of demand for building decoration materials and the emphasis on environmentally friendly production, the market demand for high-gloss wear-resistant ecological stone has been growing. However, the existing solutions for improving the gloss and wear resistance of inorganic ecological stone are limited, usually requiring the addition of surface coatings or the use of expensive additives, which increases costs and affects the overall environmental friendliness of the product. Summary of the invention

[0007] Based on the research background of the above problems, the present invention proposes a method for dry production of high-gloss wear-resistant inorganic ecological stone, which significantly improves the gloss and wear resistance of the inorganic ecological stone products, while reducing energy consumption and pollution. The production method can not only meet market demand, but also conform to the development direction of green building materials, and has important research and promotion value.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A method for dry-process production of high-gloss wear-resistant inorganic ecological stone comprises the following steps:

[0010] (1) According to the weight, 260-300 parts of cement, 120-160 parts of industrial by-product gypsum, 210-280 parts of mineral powder, 140-280 parts of industrial slag, construction waste and tailings, 140-280 parts of marble, 140-280 parts of tailings, and 42-84 parts of stone brightener are weighed and put into the mixing system, and after uniform mixing, they are conveyed to the distribution vehicle via a conveyor belt, and uniformly distributed through the automatic distribution system; then they are conveyed to the pressing station, and high-density ultra-hard inorganic ecological stone slabs are pressed by a high-efficiency hydraulic press;

[0011] (2) The above-mentioned boards are steamed in a steaming kettle for 2-3 hours, and then placed in a curing pool for curing for 2-3 days. After the curing is completed, they are finely polished and edge-grinded by an automatic polishing machine to obtain ecological stones that meet the required brightness. The finished products are packaged and stored in a warehouse.

[0012] Furthermore, the industrial by-product gypsum in the present invention is selected from at least one of desulfurized gypsum, fluorinated gypsum, phosphogypsum and titanium gypsum.

[0013] Furthermore, the marble in the present invention is selected from black marble or dolomite.

[0014] Furthermore, the tailings described in the present invention are selected from at least one of waste foundry sand, waste coated sand, waste gold ore sand, and waste copper ore sand.

[0015] Furthermore, the stone brightener of the present invention is composed of the following raw materials in a weight ratio:

[0016] Triethanolamine oleate: 32-60 parts by weight;

[0017] Methyl allyl alcohol polyoxyethylene ether: 5-10 parts by weight;

[0018] White oil: 10-20 parts by weight;

[0019] 1H,1H,2H,2H-Perfluorooctanol acrylate: 0.5-2 parts by weight;

[0020] 5-aminobenzimidazolone: ​​0.02-0.2 parts by weight;

[0021] Triethylamine: 2-5 parts by weight;

[0022] The weighed raw materials are mixed and stirred at 60-70° C. for 10-20 hours to obtain a stone brightener.

[0023] Furthermore, in the mixing process of the present invention, the main shaft speed is 30-50 rpm, and the stirring paddle linear speed is 1.5-3.0 m / s.

[0024] Furthermore, in the material distribution process of the present invention, the thickness of the plate after uniform distribution is 10 mm-350 mm.

[0025] Furthermore, the temperature during the steaming process of the present invention is controlled at 60-80°C.

[0026] Furthermore, the polishing process in the present invention uses a polishing abrasive of 800-2000 mesh.

[0027] The reaction mechanism is as follows:

[0028] Oleic acid triethanolamine and methyl allyl alcohol polyoxyethylene ether: The amino group (-NH 2 ) acts as a nucleophile to attack the carbon-carbon double bond (C=C) in methyl allyl alcohol polyoxyethylene ether, resulting in the rupture of the double bond and the formation of a new carbon-nitrogen bond (CN); triethanolamine oleate is introduced into the structure of methyl allyl alcohol polyoxyethylene ether. Similarly, the amino group of 5-aminobenzimidazolone will also undergo Michael addition reaction with the carbon-carbon double bond in methyl allyl alcohol polyoxyethylene ether.

[0029] The inorganic ecological stone slab prepared by the method of the present invention has the following advantages:

[0030] 1) Benzimidazolone and perfluoroester have excellent surfactant properties and heat resistance, which enables them to form a stable protective layer on the surface of stone, which not only improves the brightness, but also enhances the stain resistance and wear resistance of the stone. In triethanolamine oleate, due to the presence of multiple hydroxyl groups (-OH), these hydroxyl groups can form hydrogen bonds to enhance the binding force with the stone surface. This hydrogen bonding effect allows the formed brightener to adhere to the stone surface more stably, improving the brightness of the stone.

[0031] 2) The Michael addition reaction product of 5-aminobenzimidazolone and 1H,1H,2H,2H-perfluorooctanol acrylate forms a linear structure, which helps the molecules to be oriented on the surface of the stone, reducing light scattering and improving brightness. The Michael addition reaction of triethanolamine oleate and methyl allyl alcohol polyoxyethylene ether, and 5-aminobenzimidazolone and 1H,1H,2H,2H-perfluorooctanol acrylate significantly improves the brightness of artificial stone by strengthening intermolecular forces and optimizing spatial structure. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0033] Example 1

[0034] A production method of high-gloss wear-resistant inorganic ecological stone, according to the following formula: 260kg cement, 120kg desulfurized gypsum, 210kg mineral powder, 140kg calcium sulfate, 140kg dolomite, 140kg waste foundry sand and 42kg stone brightener. The main shaft speed is 30rpm and the stirring paddle linear speed is 1.5m / s for mixing, and the uniform thickness is controlled to be 10mm. After being pressed by a 5000-ton hydraulic press, it is steamed at 60°C for 2 hours and cured in a water tank for 2 days. Finally, it is polished with 800-mesh polishing abrasive to obtain a finished product with good gloss and wear resistance.

[0035] Among them, the stone brightener is prepared by weighing 60kg of triethanolamine oleate, 10kg of methyl allyl alcohol polyoxyethylene ether, 20kg of white oil, 2kg of 1H,1H,2H,2H-perfluorooctanol acrylate, 0.2kg of 5-aminobenzimidazolone, and 5kg of triethylamine, mixing them and stirring them at 65°C for 15 hours to obtain the stone brightener.

[0036] Example 2

[0037] A production method of high-gloss wear-resistant inorganic ecological stone, according to the following formula: 300kg cement, 140kg fluorgypsum, 250kg mineral powder, 180kg calcium sulfate, 160kg biotite, 160kg waste coated sand and 45kg stone brightener. The main shaft speed is 40rpm and the stirring paddle linear speed is 2.0m / s for mixing, and the uniform thickness is 12mm. After being pressed by a 5200-ton hydraulic press, it is steamed at 70°C for 2.5 hours and cured in a water tank for 2.5 days. Finally, a 1000-mesh polishing abrasive is used to polish to obtain a high-gloss ecological stone with excellent performance.

[0038] Among them, the stone brightener is prepared by weighing 40kg of triethanolamine oleate, 8kg of methyl allyl alcohol polyoxyethylene ether, 15kg of white oil, 1kg of 1H,1H,2H,2H-perfluorooctanol acrylate, 0.1kg of 5-aminobenzimidazolone, and 4kg of triethylamine, mixing them and stirring them at 68°C for 12 hours to obtain the stone brightener.

[0039] Example 3

[0040] A method for producing high-gloss wear-resistant inorganic ecological stone, according to the following formula: 280kg cement, 160kg phosphogypsum, 280kg mineral powder, 280kg calcium sulfate, 180kg dolomite, 180kg waste gold ore and 50kg stone brightener. The main shaft speed is 50rpm and the stirring paddle linear speed is 3.0m / s for mixing, and the uniform thickness is controlled to be 15mm. After being pressed by a 5500-ton hydraulic press, it is steamed at 80°C for 3 hours and cured in a water tank for 3 days. Finally, it is polished with a 2000-mesh polishing abrasive, and the finished product has high gloss and excellent hardness.

[0041] Among them, the stone brightener is prepared by weighing 50kg of triethanolamine oleate, 7kg of methyl allyl alcohol polyoxyethylene ether, 18kg of white oil, 1.5kg of 1H,1H,2H,2H-perfluorooctanol acrylate, 0.15kg of 5-aminobenzimidazolone, and 3kg of triethylamine, mixing them and stirring them at 62°C for 18 hours to obtain the stone brightener.

[0042] Example 4

[0043] A production method of high-gloss wear-resistant inorganic ecological stone, according to the following formula: 290kg cement, 130kg titanium gypsum, 260kg mineral powder, 220kg calcium sulfate, 220kg black cloud stone, 140kg waste copper ore and 55kg stone brightener. The main shaft speed is 35rpm and the stirring paddle linear speed is 2.5m / s for mixing, and the uniform thickness is controlled to be 13mm. After being pressed by a 5300-ton hydraulic press, it is steamed at 75°C for 2.5 hours and cured in a water tank for 2 days. Finally, a 1500-mesh polishing abrasive is used for fine polishing, and the product is bright and wear-resistant.

[0044] Among them, the stone brightener is prepared by weighing 45kg of triethanolamine oleate, 6kg of methyl allyl alcohol polyoxyethylene ether, 12kg of white oil, 1.2kg of 1H,1H,2H,2H-perfluorooctanol acrylate, 0.05kg of 5-aminobenzimidazolone, and 2.8kg of triethylamine, mixing them and stirring them at 69°C for 10 hours to obtain the stone brightener.

[0045] Example 5

[0046] A method for producing high-gloss wear-resistant inorganic ecological stone, according to the following formula: 270kg cement, 140kg desulfurized gypsum, 240kg mineral powder, 240kg calcium sulfate, 260kg dolomite, 160kg waste coated sand and 60kg stone brightener. The material is mixed at a spindle speed of 45rpm and a stirring paddle line speed of 2.2m / s, with a uniform thickness of 11mm. After being pressed by a 5400-ton hydraulic press, it is steamed at 65°C for 2 hours and cured in a water tank for 3 days. Finally, it is polished with a 1200-mesh polishing abrasive to obtain a high-performance ecological stone slab.

[0047] Among them, the stone brightener is prepared by weighing 35 kg of triethanolamine oleate, 9 kg of methyl allyl alcohol polyoxyethylene ether, 16 kg of white oil, 0.8 kg of 1H,1H,2H,2H-perfluorooctanol acrylate, 0.18 kg of 5-aminobenzimidazolone, and 3.2 kg of triethylamine, mixing them and stirring them at 67°C for 14 hours to obtain the stone brightener.

[0048] Example 6

[0049] A method for producing high-gloss wear-resistant inorganic eco-stone, according to the following formula: 260kg cement, 150kg fluorgypsum, 220kg mineral powder, 200kg calcium sulfate, 280kg biotite, 150kg waste foundry sand and 84kg stone brightener. The materials are mixed at a spindle speed of 40rpm and a stirring paddle linear speed of 2.0m / s, with a uniform thickness of 14mm. After being pressed by a 5000-ton hydraulic press, the materials are steamed at 60°C for 2.5 hours and cured in a water tank for 2.5 days. Finally, the materials are polished with a 1000-mesh polishing abrasive to obtain a bright and wear-resistant inorganic eco-stone.

[0050] Among them, the stone brightener is prepared by weighing 32kg of triethanolamine oleate, 5kg of methyl allyl alcohol polyoxyethylene ether, 10kg of white oil, 0.5kg of 1H,1H,2H,2H-perfluorooctanol acrylate, 0.02kg of 5-aminobenzimidazolone, and 2kg of triethylamine, mixing them and stirring them at 60°C for 20 hours to obtain the stone brightener.

[0051] Comparative Example 1

[0052] The difference between this example and Example 1 is that no stone brightener is added.

[0053] Comparative Example 2

[0054] The difference between this example and Example 1 is that 1H,1H,2H,2H-perfluorooctanol acrylate is not added during the preparation of the stone brightener.

[0055] Comparative Example 3

[0056] The difference between this example and Example 1 is that 5-aminobenzimidazolone is not added during the preparation of the stone brightener.

[0057] Detection method:

[0058] 1) Wear resistance test: Use a grinding wheel wear resistance tester to test according to GB / T 17657-2013. Place the sample under the tester, run the grinding wheel at the specified pressure and speed, and record the sample surface wear volume (mm 3 ).

[0059] 2) Brightness test: Use a gloss meter to test the gloss of the sample surface according to ASTM D523 standard (unit: GU, Gloss Unit). Clean the sample surface before testing and select 3 measurement points to take the average value.

[0060] 3) Surface hardness test: According to GB / T 2411-2008 standard, use Shore D hardness tester to measure the surface hardness of the stone and record the hardness value.

[0061] Test results:

[0062] Table 1

[0063]

[0064]

[0065] Through the above implementation, it can be seen that the protective layer generated by the chemical reaction of the stone brightener used in this method not only optimizes the molecular arrangement, reduces light scattering, and increases brightness, but also enhances the hardness and wear resistance of the stone surface, thereby greatly improving the comprehensive performance of the ecological stone slab.

[0066] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for dry production of high-gloss wear-resistant inorganic ecological stone, characterized in that: The following steps are involved: (1) According to the weight, 260-300 parts of cement, 120-160 parts of industrial by-product gypsum, 210-280 parts of mineral powder, 140-280 parts of industrial slag, construction waste and waste soil, 140-280 parts of marble, 140-280 parts of tailings, and 42-84 parts of stone brightener are weighed and put into the mixing system, and after uniform mixing, they are conveyed to the distribution vehicle via a conveyor belt, and uniformly distributed through the automatic distribution system; then they are conveyed to the pressing station, and high-density ultra-hard inorganic ecological stone slabs are pressed by an efficient hydraulic press; (2) The above-mentioned boards are steamed in a steaming kettle for 2-3 hours, and then placed in a curing pool for curing for 2-3 days. After the curing is completed, they are finely polished and edge-grinded by an automatic polishing machine to obtain ecological stones that meet the required brightness. The finished products are packaged and stored in a warehouse.

2. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The industrial by-product gypsum is selected from at least one of desulfurized gypsum, fluorinated gypsum, phosphogypsum and titanium gypsum.

3. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The marble is selected from black marble or dolomite.

4. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The tailings are selected from at least one of waste foundry sand, waste coated sand, waste gold ore sand, and waste copper ore sand.

5. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The stone brightener is composed of the following raw materials in weight ratio: Triethanolamine oleate: 32-60 parts by weight; Methyl allyl alcohol polyoxyethylene ether: 5-10 parts by weight; White oil: 10-20 parts by weight; 1H,1H,2H,2H-Perfluorooctanol acrylate: 0.5-2 parts by weight; 5-aminobenzimidazolone: ​​0.02-0.2 parts by weight; Triethylamine: 2-5 parts by weight; The weighed raw materials are mixed and stirred at 60-70° C. for 10-20 hours to obtain a stone brightener.

6. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The mixing process: the main shaft speed is 30-50rpm, and the stirring paddle linear speed is 1.5-3.0m / s.

7. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The material distribution process: the thickness of the plate after uniform distribution is 10mm-350mm.

8. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The temperature is controlled at 60-80°C during the steaming process.

9. The method for dry production of high-gloss wear-resistant inorganic ecological stone according to claim 1, characterized in that: The polishing process uses 800-2000 mesh polishing abrasive.

Citation Information

Patent Citations

  • A process for preparing inorganic eco-stones that maintain high gloss and the resulting inorganic eco-stones.

    CN114507081B

  • Artificial ecological stone slab for decoration and preparation method thereof

    CN103755278A

  • Polyurethane matrix wear-resistant stone polishing material and preparation method thereof

    CN113787468A

  • Preparation process of inorganic ecological stone capable of keeping high luminosity and inorganic ecological stone

    CN114507081A

  • Building material prepared from waste stone powder

    CN115259722A